2001
DOI: 10.1086/323792
|View full text |Cite
|
Sign up to set email alerts
|

The Masses of White Dwarfs in the Praesepe Open Cluster

Abstract: We present results from an in-depth photometric and spectroscopic study of white dwarfs in the Praesepe open cluster. From high signal-to-noise ratio spectra, we have estimated log g and for six DA T eff white dwarfs using model atmosphere Ðts to the Balmer lines. Evolutionary models are then used to determine masses, radii, and cooling times. Good agreement is found with masses determined using gravitational redshifts primarily by Reid and with masses determined from the clusterÏs distance. Included in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(133 citation statements)
references
References 36 publications
5
127
0
Order By: Relevance
“…Thus, the large spread could be explained by considering that maybe these two objects are field stars. However, the sample of white dwarfs in the Praesepe cluster has been well studied (Claver et al 2001;Dobbie et al 2004) and it is unlikely that these stars do not belong to the cluster. The Hyades contain a large number of white dwarfs, for which the initial and final masses have been derived with accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the large spread could be explained by considering that maybe these two objects are field stars. However, the sample of white dwarfs in the Praesepe cluster has been well studied (Claver et al 2001;Dobbie et al 2004) and it is unlikely that these stars do not belong to the cluster. The Hyades contain a large number of white dwarfs, for which the initial and final masses have been derived with accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…We have used the data of Claver et al (2001) for the Hyades and part of the Praesepe sample. We have included also two stars studied by Dobbie et al (2004) and some recent results of six new stars (Dobbie et al 2006).…”
Section: Other Available Datamentioning
confidence: 99%
“…It has been suggested (see, e.g., Eggen & Iben 1988 ; see also Barstow et al 1997, their°6.1) that the paradox of the hot WD in V471 Tau could be resolved if the system really is much younger than other members of the Hyades, having 5 Curiously, the Praesepe cluster also contains a high-mass WD, LB 5893, that is anomalously hot for its mass, as shown by Reid (1996), Claver, Liebert, & Bergeron (1997), and Claver et al (2001) ; although LB 5893 is a single WD, it presents a paradox similar to that of V471 Tau. Table 3 ; gravitational-redshift masses are plotted for the single white dwarfs and our dynamical mass for V471 Tau.…”
Section: Recent Star Formationmentioning
confidence: 95%
“…Clemens et al (1992) showed that the X-ray and optical modulations are 180¡ out of phase and argued that they arise because of magnetic accretion from the K dwarfÏs wind onto the pole(s) of the WD. In this picture, the WDÏs rotation period is 9.25 minutes, and metallic opacity darkens the pole(s) of the WD in soft X-rays while brightening them through Ñux redistribution in the optical (see Dupuis et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic fields, alongside angular momentum, were also proposed to be an effective factor of the mass-loss, after the discovery of a magnetic white dwarf (MWD) WD 0836+201 as a probable member of the Praesepe cluster (EG59, Claver et al 2001;Catalán et al 2008a). Note that it was mislabeled in both works as explained in Casewell et al (2009).…”
Section: Introductionmentioning
confidence: 99%